Comparison of coaches` and players` perception of training intensity: A perfect match - Brink, M. S.; Lemmink, K. A. P. M. (7th World Congress on Science and Football (WCSF), 2011, 2011)
Adequate planning of training by coaches underlies periodization in soccer. However, a lack of correspondence between the training plan designed by coaches and executed by players may result in under- or overtraining. Especially in youth soccer, training intensity is difficult to control, because of large variety in individual characteristics, e.g. body composition1. Therefore the aim of this study was to investigate the differences in perceptions of training intensity between coaches and young elite soccer players. Methods Forty young elite Dutch soccer players (U19 and U17 squad) participated in this study (height: 178.2±6.6 cm; weight: 70.5±6.4 kg; and %fat: 12.2±1.6). Prior to each training session, both coaches of the squads filled in their intended intensity (6-20 scale) on an individual level. After each session, all players scored their session Rating of Perceived Exertion. Overall correspondence between coaches and players was analysed with pearson`s correlation coefficient. In addition, three intensity levels2 as intended by the coaches, fairly easy (RPE < 13), intermediate (RPE = 13-14) and fairly hard (RPE > 14) were compared with the perceptions of players. Results & Discussion Data of 1707 training sessions were collected. A significant but low correlation between coaches` and players` scores was found (r = .34). Players perceived fairly easy and intermediate training sessions significantly harder than intended by the coach (p<0.001). The tendency of players to train harder on fairly easy and intermediate intensity levels, possibly results in maladaptation in the long run. Conclusion There are significant differences between the training plan designed by coaches and executed by the young elite soccer players.